Heritage Politics and Policies in Hindu Rashtra - Corinne Lefèvre (South Asia Multidisciplinary Academic Journal)
The present essay explores three inseparable facets of the BJP’s heritage ideology and practices: the state’s reluctance to fulfil its traditional role of guardian of the nation’s built landscape and the concomitant resort to neoliberal outsourcing strategies to fill in the gap, combined with a strong sectarian bias at work in the shrinking state-sponsored projects of patrimonial management; a strong appetite for building new and exorbitant heritage artefacts; finally, the gradual obliteration of all material traces related to the plurisecular presence of Muslims in the subcontinent through physical elimination or renaming, resulting in the growing Hinduization of India’s public space.